2010
DOI: 10.1016/j.jconrel.2009.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Endocytic uptake of a large array of HPMA copolymers: Elucidation into the dependence on the physicochemical characteristics

Abstract: Endocytic uptake and subcellular trafficking of a large array of HPMA (N-(2-hydroxypropyl) methacrylamide) based copolymers possessing positively or negatively charged residues, or hydrophobic groups were evaluated by flow cytometry and living cell confocal microscopy in cultured prostate cancer cells. The degrees of cellular uptake of various copolymer fractions with narrow polydispersities were quantified. The copolymer charge was the predominant physicochemical feature in terms of cellular uptake. Fast and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 50 publications
3
42
0
Order By: Relevance
“…42 A predominant factor for selecting different endocytotic routes seems to be the surface charge. Liu et al 25 analyzed the uptake of p(HPMA) polymer containing various positively or negatively charged groups as well as hydrophobic side chains. They demonstrated that positively charged copolymers were taken up by CME, micropinocytosis as well as dynamin-dependent endocytosis.…”
Section: Different Endocytotic Routes Of Polymer Uptakementioning
confidence: 99%
See 2 more Smart Citations
“…42 A predominant factor for selecting different endocytotic routes seems to be the surface charge. Liu et al 25 analyzed the uptake of p(HPMA) polymer containing various positively or negatively charged groups as well as hydrophobic side chains. They demonstrated that positively charged copolymers were taken up by CME, micropinocytosis as well as dynamin-dependent endocytosis.…”
Section: Different Endocytotic Routes Of Polymer Uptakementioning
confidence: 99%
“…[22][23][24] On the other hand, studies revealed that the chemical structure of polymers may also play a role for their endocytotic uptake. Liu et al 25 demonstrated that HPMA-based polymers containing alkaline side chains, eg, 2-(N,N-dimethylamino) ethyl methacrylate (positive ζ potential), were taken up by cells much stronger than polymers containing acidic adducts, eg, methacrylic acid (negative ζ potential). This mechanism could be of importance in particular in an acidic extracellular environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher level of internalization of free DOX than dendritic conjugate might be attributed to diffusion due to concentration gradients [30]. While multiple endocytosis ways were involved with cellular uptake of dendritic conjugate by 4T1 cells, and the uptake rate was much slower than free diffusion [42,43].…”
Section: Cellular Uptakementioning
confidence: 99%
“…5,6 However, there seems to be a lack of in-depth understanding of how to effectively optimize intracellular delivery because cellular uptake mechanisms and rates vary widely with the type, size, charge, and surface properties of the nanoparticles employed, and more importantly, with the cell type under study. [6][7][8][9] This, hence, makes it implausible for broad generalizations to be made, and there is therefore the need to treat each nanocarrier and cell type specifically on a case-to-case basis. In addition, the rate of cellular uptake varies with cell population density, 10,11 further making it very challenging to draw general conclusions for the enhancement of particle cellular uptake.…”
Section: Introductionmentioning
confidence: 99%